Faktor-Faktor Yang Mempengaruhi Upaya Pencegahan Dan Pengungkapan Fraud: Peran Penting Akuntansi Forensik, Dan Audit Investigasi - Elisa Khoeriyah Sukawanda; Cris Kuntadi (Journal of Islamic Economics and Finance, 2024)
Fraud is not a new disease in the global economy. This crime can even cause extraordinary losses to the business world, the country and the world. According to the ACFE, fraud costs businesses 5% of their total revenue each year. Therefore, preventative and disclosure measures are also important to address this serious problem. One of them is forensic accounting and investigative auditing. However, because it is a new field, few people understand forensic accounting and investigative auditing, still have questions about fraud, and do not know techniques for preventing and detecting fraud. This article reviews the factors that influence Fraud Prevention and Disclosure, namely Forensic Accounting and Investigative Audits, a study in the tax accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Forensic Accounting influences Fraud Prevention and Disclosure; 2) Investigative Audits influence Fraud Prevention and Disclosure.